2022
DOI: 10.3389/fphar.2021.803626
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Pembrolizumab Plus Chemotherapy Versus Pembrolizumab Monotherapy in Metastatic Non-Squamous and Squamous NSCLC Patients With PD-L1 Expression ≥ 50%

Abstract: Objective To compare the cost-effectiveness of the combination of pembrolizumab and chemotherapy (Pembro+Chemo) versus pembrolizumab monotherapy (Pembro) as the first-line treatment for metastatic non-squamous and squamous non-small-cell lung cancer (NSCLC) with PD-L1expression ≥50%, respectively, from a US health care perspective.Material and Methods A comprehensive Makrov model were designed to compare the health costs and outcomes associated with first-line Pembro+Chemo and first-line Pembro over a 20-years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Liu 2021 [ 50 ] confirmed that compared to pembrolizumab monotherapy, pembrolizumab combined chemotherapy could add 0.22 QALY to life expectancy in patients with LSCC, with a corresponding marginal incremental cost of $3,449, and $15,613 /QALY of ICER.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Liu 2021 [ 50 ] confirmed that compared to pembrolizumab monotherapy, pembrolizumab combined chemotherapy could add 0.22 QALY to life expectancy in patients with LSCC, with a corresponding marginal incremental cost of $3,449, and $15,613 /QALY of ICER.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the 10 evaluation criteria of the Drummond Checklist, 13 of the 15 cost-effectiveness analyses were evaluated with perfect scores. The remaining two studies, Liu 2022 [ 50 ] and Shao 2022 [ 53 ], received a score of 9 for not providing a calculation method of the cost discount rate over time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations